Methods used to develop the light emitting nanostructures with InGaAs/GaAs quantum wells - S. Saeid (Физика волновых процессов и радиотехнические системы, 2017)
Light-emitting diodes based on InGaAs/GaAs quantum wells (QW) were fabricated and investigated. Cover layers of GaAs (15, 25, 35 nm) were deposited by high temperature (630 ˚C) epitaxy. Ferromagnetic Co metal layer was deposited by 60 ˚C and 90 ˚C and used as a spin injector. Incorporation of a tunnel-thin barrier of Al2O3 dielectric layer between the ferromagnet and the semiconductor cover layer leads to reduce the influence Co on the luminescence intensity, which indicates the reduction of penetration of impurity and defects into active region (QW). The experimental results demonstrate that manipulating of the cover-layer thickness and of the metal-film-deposition temperature improve performance and efficiency of spin injection light-emitting diodes.